Pelatihan Komunikasi Interpersonal Terintegrasi Prinsip Kesantunan Berbahasa Guru Sekolah Dasar - Susandi, Ari; Al Ibad, M Kamal; Zativalen, Oriza; Sugiarti, Sri; Rizkia Pangestika, Rintis (Jurnal Pengabdian Masyarakat Sains Indonesia, 2024)
Interpersonal communication training integrated with the principles of language politeness aims to develop teachers' good communication skills in teaching and interacting with students so as to create a fun and communicative learning atmosphere. The method used in this training is the lecture and question and answer method. This method is carried out by providing material that is appropriate to the problems faced by the training participants. Practicals, the implementation of which goes hand in hand with the theoretical material so that practical results can be directly reflected on. Simulation, this was carried out to realize all the problems above and provide a real picture of the participants before and after the training. The training subjects for this activity were 18 Muhammadiyah I Babat Elementary School teachers. The results of the training showed a significant increase in teachers' interpersonal communication skills which did not violate the principles of language politeness at all.